Genetic architecture for skeletal muscle glycolytic potential in Chinese Erhualian pigs revealed by a genome-wide association study using 1.4M SNP array - Xie, Xinke; Huang, Cong; Huang, Yizhong; Zou, Xiaoxiao; Zhou, Runxin; Ai, Huashui; Huang, Lusheng; Ma, Junwu (Frontiers in Genetics, 2023)
Muscle glycolytic potential (GP) is a key factor affecting multiple meat quality traits. It is calculated based on the contents of residual glycogen and glucose (RG), glucose-6-phosphate (G6P), and lactate (LAT) contents in muscle. However, the genetic mechanism of glycolytic metabolism in skeletal muscle of pigs remains poorly understood. With a history of more than 400 years and some unique characteristics, the Erhualian pig is called the "giant panda" (very precious) in the world's pig species by Chinese animal husbandry. Here, we performed a genome-wide association study (GWAS) using 1.4M single nucleotide polymorphisms (SNPs) chips for longissimus RG, G6P, LAT, and GP levels in 301 purebred Erhualian pigs. We found that the average GP value of Erhualian was unusually low (68.09 µmol/g), but the variation was large (10.4–112.7 µmol/g). The SNP-based heritability estimates for the four traits ranged from 0.16-0.32. In total, our GWAS revealed 31 quantitative trait loci (QTLs), including 8 for RG, 9 for G6P, 9 for LAT, 5 for GP. Of these loci, 8 were genome-wide significant (P < 3.8×10-7), and 6 loci were common to two or three traits. Multiple promising candidate genes such as FTO, MINPP1, RIPOR2, SCL8A3, LIFR and SRGAP1 were identified. The genotype combinations of the 5 GP-associated SNPs also showed significant effect on other meat quality traits. These results not only provide insights into the genetic architecture of GP related traits in Erhualian, but also are useful for pig breeding programs involving this breed.